2004
DOI: 10.1103/physrevlett.93.176806
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Intershell Conductance in Multiwalled Carbon Nanotubes

Abstract: We report on the intershell electron transport in multiwalled carbon nanotubes (MWNTs). To do this, local and nonlocal four-point measurements are used to study the current path through the different shells of a MWNT. For short electrode separations less, similar 1 mum the current mainly flows through the two outer shells, described by a resistive transmission line with an intershell conductance per length of approximately (10 kOmega)(-1)/microm. The intershell transport is tunnel type and the transmission is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
160
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(172 citation statements)
references
References 27 publications
9
160
3
Order By: Relevance
“…In multiwalled nanotubes (MWNT) current flows only through the outermost shell as the inner shells are not electronically coupled to the metal leads [13], and inter shell hopping is negligible [22]. Here, we are interested in the role of electrostatic coupling between the inner and outer shells, in affecting the potential profile and current carried by the outer shell.…”
Section: Electrostatic Gating Due To Inner Shellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In multiwalled nanotubes (MWNT) current flows only through the outermost shell as the inner shells are not electronically coupled to the metal leads [13], and inter shell hopping is negligible [22]. Here, we are interested in the role of electrostatic coupling between the inner and outer shells, in affecting the potential profile and current carried by the outer shell.…”
Section: Electrostatic Gating Due To Inner Shellsmentioning
confidence: 99%
“…Another source of error is an overestimated bandgap [Eq. (22)] and higher threshold for the onset of current due to non crossing subbands. In this work, all our self-consistent calculations included Eq.…”
Section: Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…But recent results reveal a substantial contribution of conduction from the second wall after carriers tunnel from the outermost wall [4]. A perfect electrical contact with an MWCNT can be achieved by preparing the contact electrodes during the tube growth and this technique has shown that the conductivity of MWCNT can be several hundred times higher than that of SWCNT [5].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, contributions of inter-shell and intra-shell conductivity are of great concern. 4 Several groups observed that the current mainly flowed on the outermost shell, [5][6][7] but some groups claimed that the inner shells also contributed to the MWCNT conduction. [8][9][10] The intra-shell conduction is similar to the high conductance of a graphene sheet through π-orbital channels.…”
Section: Introductionmentioning
confidence: 99%